(untitled) (Jurnal Intek Akuakultur, 2018)
The purpose of this study was to find out how hormonal induction procedures and the quality of spawning results by observation and literature review. The time and place for testing hormone products is July 2018 at the BBI Pengujan. The research method is field observation of spawning Silver pompano fish with induction of several different hormones and reviewing literature. The research procedure included the implementation of spawning tests with 4 hormone inducers in 4 pairs of Silver pompano who were ready to spawn and conducted a literature study. The results of the study were induction of the hormone WOFA-FH, hCG Chorullon and Ovaprim spawning, while the Polaris hCG hormone did not occur spawning.